A record of the transition between Gondwana and South Atlantic crust in the tholeiitic intrusive magmatism of Cabo Frio Tectonic Domain, Southeast Brazil - Carvas, Karine Zuccolan (2022)
The transition from large igneous provinces (LIPs) into new ocean crust during early stages of rift evolution is largely unknown, and it is poorly represented or resolved in the geological record. Combining petrogenetic studies, magma dynamics investigations and novel geochronological approaches, this PhD thesis shows that early MORB- and Paraná-Etendeka-type intrusions associated with Gondwana breakup, in the Cabo Frio Tectonic Domain (Southeast Brazil), represent evidence of the initial oceanization of the South-America-Africa margins. A novel approach to 40Ar/39Ar geochronology of MORB-type dykes from the Cabo Frio Tectonic Domain was instrumental in differentiating between magmatism and post-magmatic alteration. Encapsulation procedures permitted focusing on minor and high retentivity magmatic amphibole and biotite aggregates. Incremental-heating analysis of both clear and cloudy feldspar crystals from the same sample revealed the ages of K- and Na-alteration. High-resolution elemental mapping of altered plagioclase crystals was combined with whole-rock elemental and isotopic analyses to determine elemental mobility and isotopic effects caused by hydrothermal fluid migration during tectonic evolution of the rifted margin. The intrusive age of a MORB-type dyke was determined to be 132.83 ± 0.30 Ma, i.e., late stages of Paraná-Etendeka magmatism. Altered plagioclase crystals show that K-, Na-, Rb-, Ba-, Sr-, Si-, Li-, Fe-, Pb- and light-REE-rich hydrothermal fluids percolated along the rifted margin between ~106-105 Ma and 60-30 Ma. Hydrothermalism was probably triggered by interactions between alkaline magmatism and basinal fluids in offshore basins along the southeastern Brazilian margin. Whole-rock geochemistry, Sr, Nd and Pb isotope signatures, mineral chemistry, thermobarometry, mass balance and thermodynamic models, and high-resolution elemental mapping of clinopyroxene crystals were used to model magma sources, magmatic evolution, and emplacement for MORB- and Paraná-Etendeka-type dykes. The LIP dykes are similar to low-Ti Ribeira magmas from the Paraná-Etendeka, deriving mostly from a metasomatized lithospheric peridotitic source that comprised a 1-3% ancient SCLM contribution applied to a 100-96% DMM 0-4% pyroxenite mixture. MORB-type dykes share many similarities with South Atlantic MORB and E-MORB rocks, and were generated from an asthenospheric, peridotitic source consisting of a 100-98% DMM 0-2% pyroxenite mixture with 0.2-0.4% ancient SCLM contribution. Both magmatic suites evolved mainly by plagioclase and clinopyroxene fractional crystallization under polybaric conditions. The multiple recharge events that fed MORB-type intrusive magmatism suggest a localized passive-margin system as early as ~2 Ma after peak LIP activity. Similar occurrences of subduction-influenced lithospheric and asthenospheric magma suites occur in rifts globally and indicate that crustal subductions related to continental amalgamation eventually contribute to the posterior destabilization of the continental structures.